Influence of Competence, Work Stress, and Burnout on Job Satisfaction in Tzu Chi Emergency Department - Adrianus Kanaris; Tjipto Rini; Erry Yudhya (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The Emergency Department is one of the busiest hospital units dealing with patients with various medical conditions, including high-risk patient cases requiring intensive care. This requires competent health workers. However, a stressful work environment can lead to high levels of job stress and burnout, which negatively impacts job satisfaction. This study aims to examine the effect of competence, job stress, and burnout on job satisfaction of health workers, especially doctors and nurses in the emergency room of Tzu Chi Hospital. This study used a quantitative approach with a questionnaire involving 38 respondents, analyzed using the Structural Equation Modeling (SEM) Partial Least Squares (PLS) technique through the SmartPLS application. The results showed that competence significantly affects job satisfaction, indicating that increasing competence increases job satisfaction. and competence also has a positive effect on burnout where the higher the competence, the lower the risk of burnout. In contrast, job stress and burnout have a negative influence on job satisfaction; the higher the stress and burnout, the lower the level of job satisfaction. These findings emphasize the importance of competency development as a strategic measure to reduce stress and burnout and increase job satisfaction. These results provide guidance for hospital management in designing effective competency improvement and stress management programs.